Corrosion behavior of Shape Memory Alloy in NaCl environment and recovery maintenance in Cu-Zn-Al sysytem (Fracture and Structural Integrity, 2022)
Shape memory effect (SME) and the relation with corrosion behavior of Cu-Zn-Al Smart Memory Alloys (SMAs) were investigated using different techniques: Scanning Electron Microscopy equipped with an Energy Dispersive System, X-Ray Diffraction analysis, Electrochemical Test in NaCl solutions with different concentrations (0.035%, 0.35% and 3.5%), which simulate coastal conditions, mechanical characterization through tensile test and guided bend test. SMAs are an important class of smart materials able to recover after deformation a pre-imposed shape through a temperature modification. These alloys show great potential, finding several applications in medicine and in different types of industry sectors (aerospace, architecture, automotive etc.). Cu-based SMAs, including Cu-Zn-Al alloys, have lower production costs with respect to Ni-Ti alloys as well as good possibility in seismic and architectural applications. A Cu-Zn-Al alloy with a theoretical composition of 25 wt.% Zn and 4 wt.% Al was produced by casting method.The aim of this study is to characterize the microstructure, the mechanical properties and the corrosion behavior through different kind of standard corrosion tests of this alloy and to evaluate the effect of corrosion damage on the shape memory recovery capability through a combination of corrosion and thermos-mechanical cyclic test and SEM observation
Keywords: Cu-Zn-Al- alloy; Shape Memory Effect; Electochemical Test; Corrosion; Shape recovery